Analysis of The Jakarta Public Satisfaction Index (IKM) During The Covid-19 Pandemic, Quarter IV of 2021 on Public Services In The Investment Management Unit and One-Door Integrated Services (Dpmptsp) at The Urban Village Level, Jakarta Province - Abdul Gafur, Ridwan; Rivai Zainal, Veithzal; Hakim, Aziz (Green Publisher, 2023)
This study aims to analyze the level of satisfaction of the people of DKI Jakarta with the implementation of public services during the Covid 19 pandemic in 2021, especially services at the Urban Village level. The level of community satisfaction was analyzed through a survey conducted on 3,510 respondents from all areas in Jakarta. This research uses a quantitative method, while the community satisfaction survey uses an interview method using a computer via the jakevo.jakarta.go.id website or commonly known as Computer Assisted Web interviewing, for 107 permits and non-permits surveyed. In this way, the characteristics of each service level will be known, making it easier for service managers to know the strengths and weaknesses of the services provided to the public. The results of the study indicate that there is a need for efforts to maintain the quality of existing services, by making efforts to consistently improve service quality. Services that need to be maintained are not charged outside the provisions and what needs to be improved is that Jakevo information is clear and easy to understand.